2003
DOI: 10.1080/02841850312331287739
|View full text |Cite
|
Sign up to set email alerts
|

MR analysis of the transverse ligament in the late stage of whiplash injury

Abstract: Whiplash trauma can damage the transverse ligament. By use of high-resolution proton-weighted MR images such lesions can be detected and classified. The reliability of this classification still needs improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 23 publications
0
40
1
Order By: Relevance
“…In one cohort, a considerable part of patients with chronic WAD were observed to have lesions in the upper cervical ligaments as visualised on MRI of the craniovertebral junction [21][22][23]. This study indicated that the alar and transverse ligaments as well as tectorial and posterior atlanto-occipital membranes can be damaged by whiplash injuries.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…In one cohort, a considerable part of patients with chronic WAD were observed to have lesions in the upper cervical ligaments as visualised on MRI of the craniovertebral junction [21][22][23]. This study indicated that the alar and transverse ligaments as well as tectorial and posterior atlanto-occipital membranes can be damaged by whiplash injuries.…”
mentioning
confidence: 77%
“…A fourth consideration is that having known more recent results demonstrating signs of injury to the upper cervical ligaments in chronic whiplash-associated disorders [15,[21][22][23] when planning this study, we would have focused more upon the upper cervical spine. The importance of upper ligament injuries should be evaluated in future prospective trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study was further excluded after detailed screening of full text articles because the comparison was performed in quantitative date of signal alterations of the transverse ligament [32], not qualitative date in other studies. Another two papers by the same authors, evaluating alar and transverse ligaments, respectively, shared the same subjects, thus were combined and considered as one study [20,23]. Because MRI scan protocol and evaluation criteria for ligament changes used in the paper by Lindgren et al [24] (1.5 T dynamic kine MRI and two-point grading scale and movement) was completely different from other six papers (1.5 T fast spin-echo proton density-weighted sequences and four-point grading scale), this paper was excluded in order to minimize clinical bias.…”
Section: Resultsmentioning
confidence: 99%
“…These structures could be well visualized by magnetic resonance imaging (MRI) [17][18][19]. In recent years, with the development of more detailed MRI techniques morphologic changes of the ligaments and membranes in the craniocervical junction, especially alar and transverse ligaments have been discussed [18,[20][21][22][23][24][25][26][27]. However, most of these studies include relatively small samples of patients and thus their results were inconsistent and lacked statistical strength.…”
Section: Introductionmentioning
confidence: 99%